2022
DOI: 10.1002/maco.202213229
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study on the effect of Ni atoms on the crack arrest performance of Fe–Ni alloy

Abstract: Molecular dynamic simulations are applied to test the nickel's modification mechanism of Fe-Ni alloy. Mono displacement loading is applied to a perfect single crystal model, a single crystal model with vacancies, and a model with transgranular crack. Moreover, constant strain load is applied to the polycrystal model to test the Ni effect on intergranular crack initiation. The results elucidate that Ni atoms could decrease the free surface energy and the stacking fault energy simultaneously. However, Ni atoms h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, Cr, Ni and other elements [15,16] played a significant role in inhibiting HE. For example, Yang et al [17] found that Ni atoms could decrease the free surface energy and the stacking fault energy simultaneously. The findings suggested that a low concentration of Ni might degrade the physical property of Fe-Ni alloy, and the increasing the Ni atomic concentration above specific critical values, e.g., 0.03 or 0.05, could enhance the fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cr, Ni and other elements [15,16] played a significant role in inhibiting HE. For example, Yang et al [17] found that Ni atoms could decrease the free surface energy and the stacking fault energy simultaneously. The findings suggested that a low concentration of Ni might degrade the physical property of Fe-Ni alloy, and the increasing the Ni atomic concentration above specific critical values, e.g., 0.03 or 0.05, could enhance the fracture toughness.…”
Section: Introductionmentioning
confidence: 99%